A pilot randomized clinical trial assessing the effect of cricoid pressure on risk of aspiration. (21st June 2016) - Bohman, J. Kyle; Kashyap, Rahul; Lee, Augustine; He, Zhaoping; Soundar, Sam; Bolling, Laura L.; Kor, Daryl J.
Abstract: Introduction: Patients at risk for microaspiration during elective intubation often receive cricoid pressure in the hopes of mitigating such risk. However, there is scarce evidence to either support or reject this practice. The objective of this investigation was to assess the effect of cricoid pressure on microaspiration and to inform the potential feasibility of conducting a larger, more definitive clinical trial. Methods: This was a pilot randomized clinical trial set in the operating rooms of a tertiary referral hospital between August and October of 2014. Patients with risk factors for microaspiration (obesity, gastroesophageal reflux disease, or diabetes) were enrolled. The patients were randomized to either cricoid pressure or no cricoid pressure during induction of anesthesia with endotracheal intubation. Immediately after intubation, a sample of lower airway secretions was collected and analyzed for pepsin A. Main Results: A total of 95 patients were evaluated, randomized and completed the study protocol. 46 were randomized to cricoid pressure and 49 to no cricoid pressure. Seven patients crossed‐over treatment arms. A total of 18 (19.6%) patients met the pre‐defined criteria for microaspiration. In both the intention‐to‐treat and per‐protocol analyses, there were no statistically significant differences in the rate of microaspiration [OR (95% CI)] = 1.39 (0.49–3.92) and 1.30 (0.44–3.86), respectively. Conclusions: Utilizing pepsin A as a biomarker of aspiration, this pilot clinical trial did not find evidence for a reduced rate of aspiration or adverse clinical events with the administration of cricoid pressure during elective endotracheal intubation of patients with risk factors for microaspiration.